The role of environmental performance in mediating the relationship between green accounting and corporate social responsibility - Dwi Ratmono; Rasid Mail; Nur Cahyonowati; Dyah N. A. Janie (ResearchGate, 2024)
The problems of pollution, global warming, and environmental damage are currently relevant and vital challenges for corporations, governments, and society. The implementation of green accounting is one of the responses of corporations to overcome sustainability issues. This study aims to examine the impact of green accounting on the level of environmental performance and the impact of environmental performance on corporate social responsibility (CSR) disclosure. This study also tests the role of environmental performance as a mediating variable in the relationship between green accounting and CSR disclosure. The sample consists of 95 listed Indonesian firms during the period 2017–2021. The results show that the adoption of green accounting positively affects environmental performance (coefficient is 0.291 and p-value < 0.01). Meanwhile, environmental performance positively affects CSR disclosure with a coefficient of 0.296 and a p-value < 0.01. The empirical evidence also shows that environmental performance has a critical role as a mediating variable in the effect of green accounting on CSR disclosure.